The impact of relationship marketing on the competitiveness of business organizations: An analytical study for a number of private Iraqi banks - Hassan Mohammed*, Reham; Ali AL-Ameri, Sarah (Journal of Economics and Administrative Sciences, 2024)
The research aims to demonstrate the impact of relationship marketing with its dimensions (trust, commitment, and satisfaction) in achieving the competitiveness of business organizations with its dimensions (market share, flexibility, and productivity and profitability) for a number of private Iraqi banks in Baghdad. One of the most important justifications for conducting the research is the need for banks to enhance the use of relationship marketing methods, and the importance of the research lies in attracting the attention of decision-makers in the researched banks to the need to pay attention to relationship marketing to achieve a competitive position in the banking business environment. The main hypothesis was formulated to measure the effect between the research variables. The descriptive analytical method was used to achieve these tests. A questionnaire was designed and distributed to a random sample of administrative leaders (members of the board of directors) in the investigated banks to collect the necessary data. The data was analyzed using the statistical program (SPSS.V.25), and one of the most important findings of the research is that there is an influence relationship between relationship marketing in its dimensions and the competitiveness of business organizations.Paper type: Research paper